An Evaluation of Implementation of Strategies for Gender Equality in the Institutions of Vocational and Higher Education of European Community - Šidlauskienė, Virginija; Eitutytė, Daina (Sociologija. Mintis ir veiksmas, 2004)
The aim of the article is to discuss the possibilities to evaluate the effectiveness of gender mainstreaming in the institutions of professional and continuing education in the form of a virtual network. The article develops a discussion of the methodological issues of the conception of NET31REM that is based on the use of information and communication technologies to create an international network through seminars, conferences, and surveys.
Keywords: gender mainstreaming; evaluation of implementation of gender mainstreaming; institutions of education